(untitled) (Annals of Bangladesh Agriculture, 2021)
The study was aimed to enumerate the load of psychrotrophic bacteria in raw milk stored in freezer. Raw milk was collected from 18 different sized dairy farms located in Gazipur and Mymensingh district. From each location equal number (three of each) of small, medium or large farms were randomly selected. The raw milk samples were stored in freezer (-18 to -22 oC) for 28 days and analyzed for psychrotrophic bacterial load at every 7 days interval. For total viable count, bacteria was grown onto plate count agar at 70C for 10 days. Bacteria grown under such conditions referred as psychrotrophs. However, to determine the type of psychrotrophs selected colonies were grown further onto pseudomonas agar base and gram staining, oxidase, catalase and methyl red test for each isolate were perfomed. The psychrotrophic bacterial load in all the samples were low until 14 days of storage. However, from the third week of storage the bacterial load was observed to increase which reached to as high as 1.1 ± 2.3×107 cfu/mL at the end of the storage period (28 days). The milk samples obtained from large farms were lower (1.3×105 to 6.6×106) than that of medium (1.7×105 to 8.8×106) and small (2.0×105 to 1.1×107) type farms. The bacterial load was significantly (P<0.01) varied among the samples suggesting the heterogeneous management practices in dairy farms. All the morphological and biochemical tests confirmed the isolates as pseudomonas. Based on the present findings, it could be suggested that raw milk can store in the freezer maximum for two weeks in terms of psychrotrophic bacterial load. Ann. Bangladesh Agric. (2020) 24(1) : 65-76